Genome Assembly and Genome Annotation of Leishmania martiniquensis Isolated from a Leishmaniasis Patient in Thailand - Songtham Anuntakarun; Atchara Phumee; Vorthon Sawaswong; Kesmanee Praianantathavorn; Witthaya Poomipak; Rungrat Jitvaropas; Padet Siriyasatien; Sunchai Payungporn (Journal of Parasitology Research)
Leishmaniasis is a parasitic disease caused by Leishmania spp. with worldwide distribution. Autochthonous leishmaniasis has been reported to result from the infection by Leishmania martiniquensis in Thailand. This species was isolated in culture and subjected to high-throughput whole-genome sequencing. A total of 30.8 Mb in 36 chromosomes of the whole genome was assembled, annotated, and characterized. The L. martiniquensis under study was shown to segregate into the same clade and thus closely related to the previously identified L. martiniquensis (LU_Lmar_1.0), as determined by phylogenetic analysis of their genomic sequences along with those of representative kinetoplastid species. The total number of open reading frames genomewide predicts 8,209 protein-coding genes, of which 359 are putative virulence factors, including two previously known, e.g., cysteine proteinase C and superoxide dismutase B1. The results obtained from this study will be useful for further annotation and comparison with other Leishmania martiniquensis in the future.